Meeting psychosocial and health information needs to ensure quality of cancer care in outpatients. (August 2017) - Piazza, Maria Francesca; Galletta, Maura; Portoghese, Igor; Pilia, Ilaria; Ionta, Maria Teresa; Contu, Paolo; Mereu, Alessandra; Campagna, Marcello
Abstract: Purpose: The purpose of this study was to investigate patients' and caregivers' health needs for a re-orientation program based on principles of health promotion in an Oncology Department from an Italian University Hospital. Method: A Cross-sectional design with qualitative and quantitative approaches was used. Participants included cancer patients and their caregivers. Information about disease concerns were collected using a survey form. Information about healthy lifestyle was obtained using motivational interviews. Information about perceived quality of oncology services was collected by a self-administered questionnaire. Results: A total of 403 information requests were collected about patients' disease, 203 motivational interviews were carried out, and 219 questionnaires were collected. Overall, the results showed that patients and caregivers have healthy lifestyles even if meat consumption was high. Weak points were: poor physical space organization in the Service, long waiting times, and limited access to healthcare providers for patients. Conclusions: This study revealed the need for an approach based on health-promotion principles, with a particular focus on patient wellbeing and quality of life. The study increases awareness about the influence that an environment has on patient health, thus suggesting that changes in culture, attitude, and health services re-organization are crucial to meet total needs of the individual as a whole process. Highlights: Satisfying needs of cancer patients/caregivers improving participation in the care process. Ensuring the access to health information and psychological support, beyond treatment. Improving collaboration within existing health services in the community. Improving the information exchange between physicians/nurses and patients/caregivers. Improving the management of organizational and structural aspects of the oncological services.